A study on rare-earth Laves phases for magnetocaloric liquefaction of hydrogen. (December 2022) - Liu, Wei; Bykov, Eduard; Taskaev, Sergey; Bogush, Mikhail; Khovaylo, Vladimir; Fortunato, Nuno; Aubert, Alex; Zhang, Hongbin; Gottschall, Tino; Wosnitza, Jochen; Scheibel, Franziska; Skokov, Konstantin; et al.
Highlights: 1 Comparative study on the rare-earth-based Laves phases R Al2 and R Ni2. 2 Observation that second-order magnetocaloric effect can be much stronger near the boiling point of hydrogen. 3 Revealing the correlations between the maximum magnetocaloric effect and the Curie temperature. Abstract: We are witnessing a great transition towards a society powered by renewable energies to meet the ever-stringent climate target. Hydrogen, as an energy carrier, will play a key role in building a climate-neutral society. Although liquid hydrogen is essential for hydrogen storage and transportation, liquefying hydrogen is costly with the conventional methods based on Joule-Thomas effect. As an emerging technology which is potentially more efficient, magnetocaloric hydrogen liquefaction can be a "game-changer". In this work, we have investigated the rare-earth-based Laves phases R Al2 and R Ni2 for magnetocaloric hydrogen liquefaction. We have noticed an unaddressed feature that the magnetocaloric effect of second-order magnetocaloric materials can become "giant" near the hydrogen boiling point. This feature indicates strong correlations, down to the boiling point of hydrogen, among the three important quantities of the magnetocaloric effect: the maximum magnetic entropy change Δ S m m a x, the maximum adiabatic temperature change Δ T a d m a x, and the Curie temperature T C . Via a comprehensive literature review, we interpret the correlations for a rare-earth intermetallic series as two trends: (1) Δ S m m a x increases with decreasing TC ; (2) Δ T a d m a x decreases near room temperature with decreasing T C but increases at cryogenic temperatures. Moreover, we have developed a mean-field approach to describe these two trends theoretically. The dependence of Δ S m m a x and Δ T a d m a x on T C revealed in this work helps researchers quickly anticipate the magnetocaloric performance of rare-earth-based compounds, guiding material design and accelerating the discoveries of magnetocaloric materials for hydrogen liquefaction. Graphical abstract: Image, graphical abstract